Ekplorasi Visual Desain Poster Kisah Maulid Nabi Muhammad SAW - Rachel Jihan Al Jauza; Mahimma Romadhona (Journal of Creative Student Research, 2023)
The visual exploration in the poster design for the story of the Prophet Muhammad SAW's birthday illustrates an effort to present a rich and meaningful narrative through graphic elements. This design combines historical and contemporary elements, where this poster attempts to build a connection between the historical meaning of the Prophet's birthday and how it is celebrated in modern times. Through visual analysis, we identify aesthetic and symbolic elements with traditional values ​​while reflecting a visual identity that is acceptable in modern society. This poster not only functions as a medium of information, but also as a tool to celebrate and maintain the celebration of the Prophet's birthday in everyday life.